Community-Acquired Pneumonia in Children: Myths and Facts - Yun, Ki Wook; Wallihan, Rebecca; Juergensen, Alexis; Mejias, Asuncion; Ramilo, Octavio (American Journal of Perinatology, 2019)
Community-acquired pneumonia (CAP) is the leading cause of death in children < 5 years of age worldwide. It is also one of the most frequent infectious diseases in children, leading to large antibiotic use and hospitalization even in the industrialized countries. However, the optimal management of CAP in children is still not well defined. Currently, respiratory viruses are considered the most frequent etiologic agents, but detection of viruses in the upper respiratory tract does not guarantee causation of pneumonia, nor precludes the presence of a bacterial pathogen. In both the upper and lower respiratory tract, respiratory viruses and pathogenic bacteria interact. Emerging evidence indicates that dual viral–bacterial infections function synergistically in many cases and together likely enhance the severity of CAP. Therefore, new and advanced technologies capable of sensitively and specifically discriminating viral, bacterial, and viral–bacterial coinfections are needed. Instead of focusing on the pathogen, analysis of host immune transcriptome profiles from children with CAP can potentially offer diagnostic signatures, help to assess disease severity, and eventually, prognostic indicators. An optimized management strategy by using molecular pathogen testing and transcriptome profiling will facilitate prompt, more appropriate, and targeted therapies, which in turn will lead to improved clinical outcomes in children with CAP.
Keywords: community-acquired pneumonia; children; transcriptional profiles; biomarkers